PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF BERBASIS LECTORA INSPIRE PADA PELAJARAN INSTALASI PENERANGAN LISTRIK DI SMK SWASTA DWIWARNA MEDAN - Anwar Saleh; Sahat Siagian (JEVTE: Journal of Electrical Vocational Teacher Education, 2021)
Abstract The purpose of this research is to develop interactive learning multimedia in the form of an interactive CD, using several software including Lectora Inspire, Adobe Photoshop CS6, Bandycam, and AMR to MP3 Converter. This development research used the Borg and Gall research model adapted from Sugiyono. The target of this research is the Expert Lecturer at the State University of Medan. The eligibility test of interactive learning multimedia was carried out by media validators, material validators, and acceptance validators. Based on the data analysis conducted, it shows that the resulting learning multimedia is good with a score of 4.4 for material validation, a score of 4.5 for media validation, and a score of 4.2 for validation of acceptances. So the results of the validation show that the learning multimedia developed is eligible for use. Key Words: Interactive Multimedia, Lectora Inspire Software, Electrical Lighting Installation AbstrakTujuan dari penelitian ini adalah mengembangkan multimedia pembelajaran interaktif dalam bentuk CD interaktif, menggunakan beberapa software diantaranya Lectora Inspire, Adobe Photoshop CS6, Bandycam, dan AMR to MP3 Converter. Penelitian pengembangan ini menggunakan model penelitian Borg and Gall yang diadaptasi dari Sugiyono. Sasaran penelitian ini adalah Dosen Ahli Universitas Negeri Medan. Uji kelayakan multimedia pembelajaran interaktif dilakukan oleh validator media, validator materi, dan validator penerimaan. Berdasarkan analisis data yang dilakukan menunjukkan bahwa multimedia pembelajaran yang dihasilkan baik dengan skor validasi materi 4,4, validasi media skor 4,5, dan validasi penerimaan skor 4,2. Sehingga hasil validasi menunjukkan bahwa multimedia pembelajaran yang dikembangkan layak untuk digunakan.Kata Kunci: Multimedia Interaktif, Software Lectora Inspire,  Instalasi Penerangan Listrik